‘The hunting-field and its doings’: subjectivities of territory of the |Xam Bushmen of the northern Cape - Guenther, Mathias (Southern African Humanities, 2020)
This paper focuses on the nineteenth-century |Xam of the northern Cape to examine the relationship of people to the environment beyond techno-economic parameters. As a lived-in, engaged-with Umwelt, the landscape becomes socially and culturally inscribed and patterned, thereby subjectivizing its features. Two ways in which this epistemological and ontological process plays itself out in the case at hand are considered—in terms of human/other-than-human relationality, and in terms of mythological imprints on the landscape. Also considered are certain epistemological implications of these anthropocenic processes for San cosmology, specifically its core feature of ontological ambiguity and mutability. KEY WORDS: relational ontology, San mythology, cosmology and rock art, taskscape, religion and ecology, onto-epistemology